Synthesis and Characterization of Thorium(IV) Complexes with Salicylaldehyde N(4)-Phenylthiosemicarbazone - Rajendran, G.; Amritha, C.S. (Asian Journal of Chemistry, 2010)
Some thorium(IV) complexes with salicylaldehyde N (4)-phenylthiosemicarbazone (SPT) were synthesized and characterized. The compositions of the complexes were ascertained from elemental analysis, molar conductivity measurements and spectral investigations to be [ThL2Xn] (X = NO3–, NCS–, ClO4–,CH3COO– or CH3 CHOHCOO–, n = 2 and X = SO42-, C2O42-, n = 1 and L = salicylaldehyde N (4)-phenylthiosemicarbazone). Thermal studies were conducted on two representative complexes. The ligands along with a few complexes were screened for their antifungal activity against Fusarium oxysporum which causes wilt in tomato.